Pengaruh Model Role Playing Berbantuan Media Boneka Tangan Terhadap Ketrampilan Berbicara Pada Kelas IV SD Negeri Surodadi 3 Candimulyo - Lestari, Dwi Puji (Prosiding University Research Colloquium, 2021)
This study aims to determine students’ speaking skills through learning role playing models assisted by hand puppet media to fourth grade students at SD Negeri Surodadi 3 Candimulyo.This study uses a pre-experimental type one group pretest posttest. Sampling in this study used a saturated sampling technique. The method of data collection is done by using a performance appraisal technique. The validation test of the performance assessment instrument was carried out using expert validation. Analysis of the data used in this study using parametric statistical techniques, namely the Paired Sample T-Test test with the help of the IBM SPSS statistic 22 application program for window. The results of data analysis using the Paired Sample T-Test obtained a value of Sig (2-tailed) < 0.005. Based on the results of data analysis, the average pretest value was 53 while the posttest value was 63 with an average difference of 10. From the results of the study, it can be concluded that the use of role playing learning models assisted by hand puppet media has an effect on students’ speaking skills.